Renal function adaptation up to the fifth decade after treatment of children with unilateral renal tumor: A cross‐sectional and longitudinal study. Issue 9 (20th April 2013) - Cozzi, Denis A.; Ceccanti, Silvia; Frediani, Simone; Mele, Ermelinda; Cozzi, Francesco
Abstract Background Mild‐to‐moderate renal function loss may be an independent risk factor for cardiovascular disease and overall mortality. As in adults with renal carcinoma nephrectomy is associated with an high risk for moderate renal function loss, we aimed to assess the renal function adaptation over a long period of time in children with unilateral renal tumor (URT). Procedure Seventy‐two children who underwent surgery for URT were enrolled in this study. Glomerular filtration rate was estimated (eGFR) with the Modification of Diet in Renal Study or the Schwartz equation, as appropriate for the age. Results Twelve patients treated by nephron‐sparing surgery (Group A) and 42 treated by nephrectomy (Group B) had an age between 2 and 30 years; 18 patients treated by nephrectomy had an age between 33 and 51 years (Group C). At cross‐sectional follow‐up 8% patients of Group A, 42% of Group B and 78% of Group C presented a mild‐to‐moderate renal function. The longitudinal data stratified by post‐operative intervals showed that patients of Group C presented a significant progressive decrease in mean ± standard deviation eGFR (88.1 ± 22.6 during the third decade after surgery vs. 66.6 ± 15.6 ml/min/1.73 m2 during the fifth decade after surgery; P = 0.02). The longitudinal data stratified by age showed that patients with an age between 45 and 54 years presented a mean eGFR significantly lower than that expected for the physiological renal function decline with aging (P = 0.001). Conclusion Aging is associated with a mild‐to‐moderate renal function loss in many adult patients following nephrectomy during childhood for URT. Pediatr Blood Cancer 2013;160:1534–1538. © 2013 Wiley Periodicals, Inc.